Self-reported Adverse Effects in Health Care Professionals Following First and Second Dose Vaccination Against SARS-CoV 2 (Covishield) - Rayamajhi, Heleena; Kaudinnyayana, Sammodavardhana; Khadka, Anjan; Sen Malla, Sudha (Medical Journal of Shree Birendra Hospital, 2022)
Introduction: The ChAdOx 1 n Cov-19 vaccine, called Covishield, was rolled out in Nepal targeting health care professionals. The study was conducted to assess the pattern of self-reported adverse events following immunization and to compare AEFI on the basis of previous COVID status. Methods: A cross sectional study of four months duration was conducted in Shree Birendra Hospital, a tertiary care hospital, in Kathmandu, Nepal. AEFI associated with first and second dose of Covishield were assessed for a period of seven days from the day of vaccination in health care professionals and comparison was done based on COVID status. Results: A total of 100 vaccine recipients were included in the study, out of which 83% showed AEFI. The most commonly reported AEFI after first dose were headache (56%), injection site tenderness (42%), myalgia (29%), fatigue (24%), dizziness (20%), pyrexia (19%), malaise (17%), nausea (10%), chills (8%), vomiting (2%) and arthralgia (1%) while among the AEFI after second dose were injection site tenderness (36%), headache (15%), myalgia (12%), fatigue (11%), nausea (9%), malaise (8%), pyrexia (8%), chills (5%), rashes (3%), drowsiness (3%), arthralgia (1%) and dizziness (1%). Previously infected participants were found to be prone to develop systemic adverse effects. The most of the adverse effects were subsided within four days and commonly used medication was paracetamol to relieve the symptoms. Conclusions: AEFI following the first and second dose of vaccine were mild. Systemic adverse effects were more frequent in those with the history of COVID-19 infection.